Numerical investigation of the effect of constant velocity and constant residence time scaling criteria on the natural gas MILD combustion - Niwat SUKSAM; Jarruwat CHAROENSUK (My University, 2019)
This paper concerns with effect of scaling on performance of MILD combustor when increasing its geometry and thermal throughput from the 0.58 MW prototype to its scaled-up versions of 5.8 MW. The constant velocity (CV) and constant residence time (CRT) scaling approaches were used in this work. Their performances were simulated with a numerical model for MILD combustion which was thoroughly validated against existing experimental data. It was found that despite MILD condition could be successfully maintained with both scaling approaches up to the scaling factor of 10, the effect of CV scaling could lead to elevated NOX emission due to increase in flow retention time in hot environment. The results were also discussed in term of Damköhler number. Despite of promising technology of MILD combustion for low-NOX emission, care must be taken on NOX emission level when scaling up with large scale factor under the CV criteria. As for the CRT criteria with increasing inlet velocity with the scale factor, the fuel and air supply pressure should be considered as a constrain when scaling up with large scale factor.
Keywords: Scale factor (cosmology); Constant (computer programming); Combustion and flame dynamics